Chromatically unique 6-bridge graph theta(a,a,a,b,b,c) - N.S.A. Karim; Roslan Hasni; Gee-Choon Lau (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2016)
For a graph G, let P(G,λ) denote the chromatic polynomial of G. Two graphs G and H are chromatically equivalent if they share the same chromatic polynomial. A graph G is chromatically unique if for any graph chromatically equivalent to G is isomorphic to G. In this paper, the chromatically unique of a new family of 6-bridge graph θ(a,a,a,b,b,c) where 2abc is investigated.